2014
DOI: 10.1111/oik.01502
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term study of root biomass in a biodiversity experiment reveals shifts in diversity effects over time

Abstract: Biodiversity experiments generally report a positive effect of plant biodiversity on aboveground biomass (overyielding), which typically increases with time. Various studies also found overyielding for belowground plant biomass, but this has never been measured over time. Also, potential underlying mechanisms have remained unclear. Differentiation in rooting patterns among plant species and plant functional groups has been proposed as a main driver of the observed biodiversity effect on belowground biomass, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
246
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 201 publications
(271 citation statements)
references
References 51 publications
24
246
1
Order By: Relevance
“…In contrast, the positive plant diversity effect on soil carbon storage (Table 1), root biomass 39 and soil microbial biomass 40 was also found for deeper soil layers in The Jena Experiment. Despite the consistency of the plant diversity effect, it may be strongest in the topsoil and decrease with soil depth 25,39 , which may be due to the fact that root carbon inputs 24,39 and microbial activity 41 decrease with soil depth. Therefore, the mechanism proposed for the topsoil is very likely to also be relevant for deeper soil layers, but the decreased biological activity at the deeper soil layers has to be taken into account.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast, the positive plant diversity effect on soil carbon storage (Table 1), root biomass 39 and soil microbial biomass 40 was also found for deeper soil layers in The Jena Experiment. Despite the consistency of the plant diversity effect, it may be strongest in the topsoil and decrease with soil depth 25,39 , which may be due to the fact that root carbon inputs 24,39 and microbial activity 41 decrease with soil depth. Therefore, the mechanism proposed for the topsoil is very likely to also be relevant for deeper soil layers, but the decreased biological activity at the deeper soil layers has to be taken into account.…”
mentioning
confidence: 85%
“…Eisenhauer et al 20 and Ravenek et al 39 showed that plant species richness was not closely linked to basal respiration and root standing biomass in the first years of the experiment; therefore, we did not use data from the first 2 years in the present analyses. Missing values were replaced by the mean.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is now consensus among ecologists that in general monocultures perform less well than plant species mixtures (Cardinale et al 2012), the main underlying mechanisms remain debated. On one hand, ecologists have focused on plant-plant interactions, with resource partitioning and facilitation between plants as the most likely explanations for the differential plant productivity (Jesch et al 2018;Mueller et al 2013;Ravenek et al 2014;Wright et al 2017). On the other hand, interactions between plants and pathogenic soil biota have emerged as an important mechanism for the positive biodiversity effect (de Kroon et al 2012;Maron et al 2011;Mommer et al 2018;Schnitzer et al 2011).…”
Section: Agalinis Gattingeri Aletris Farinosa Gentiana Alba Liatris Smentioning
confidence: 99%
“…The spread of Phytopthora blight between pepper rows was reduced with a higher degree of root intermingling and even totally blocked in the treatment with the tightest root intermingling. Root systems in species-rich grassland communities are often dense and tightly intermingled as well (Kesanakurti et al 2011;Ravenek et al 2014;Frank et al 2015), thus potentially reducing spread of fungal pathogens.…”
Section: Direct Neighbour Effects Via Plant Traits and Root Exudatesmentioning
confidence: 99%